2008
DOI: 10.2298/hel0849103t
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid seed production in detergent induced male sterile Helianthus annuus L.

Abstract: Efficacy of a synthetic detergent "Surf Excel" as a potential male gametocide in Helianthus annuus was evaluated. Foliar applications of three concentrations of "Surf Excel" solution (1.0, 2.0 and 3.0% w/v) at different plant development stages caused reduction in plant height, pollen fertility, total yield/ plant, 100-seed weight and brought about early flowering in comparison with control plants. All treatments with "Surf Excel" solution caused elongation of the style in floral buds resulting in protrusion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Detergents also have proven effective in induction of sterility of the pollen in crops like mustard, rice (Chauhan and Vandana Singh, 2002), and niger (Gangaprasad et al, 2004) at different concentrations (1 to 6 %). Complete and long-lasting sterility (91-99 %) was reported by foliar application of surf excel in lentil (Singh, 2017) and 99.87% pollen sterility in sunflower without effecting the production in sunflower, the treatment led to elongation of the style in floral buds (Tripathi and Singh, 2008). Plant growth regulators (PGR) has also been reported to target the male organ.…”
Section: Chemical Hybridizing Agents (Chas)mentioning
confidence: 99%
“…Detergents also have proven effective in induction of sterility of the pollen in crops like mustard, rice (Chauhan and Vandana Singh, 2002), and niger (Gangaprasad et al, 2004) at different concentrations (1 to 6 %). Complete and long-lasting sterility (91-99 %) was reported by foliar application of surf excel in lentil (Singh, 2017) and 99.87% pollen sterility in sunflower without effecting the production in sunflower, the treatment led to elongation of the style in floral buds (Tripathi and Singh, 2008). Plant growth regulators (PGR) has also been reported to target the male organ.…”
Section: Chemical Hybridizing Agents (Chas)mentioning
confidence: 99%
“…Kaymak and Gökalp Muranli (2005) concluded that when soaking onion roots in 0.1, 0.2, 0.3, and 0.4% of Avenoxan (the commercial compound of the herbicide 2,4-D) and for several periods (6-12-24 hours), the chromosomal abnormalities increased with the increment of concentration and duration of treatment, and consequently the proportion of sterile pollen grains increased. Tripathi and Singh (2008) showed that washing powder succeeded in producing male sterility in several plant species when treated with low concentrations, while high concentrations caused a great abnormality. This is also consistent with Singh (2005) findings.…”
Section: Introductionmentioning
confidence: 99%